The Basolateral Amygdala to Ventral Hippocampus Circuit Controls Anxiety-Like Behaviors Induced by Morphine Withdrawal - Deji, Cuola; Yan, Peng; Ji, Yuanyuan; Yan, Xinyue; Feng, Yue; Liu, Jincen; Liu, Yige; Wei, Shuguang; Zhu, Yongsheng; Lai, Jianghua (Frontiers in Cellular Neuroscience, 2022)
Anxiety is one of the most common comorbid conditions reported in people with opioid dependence. The basolateral amygdala (BLA) and ventral hippocampus (vHip) are critical brain regions for fear and anxiety. The kappa opioid receptor (KOR) is present in the mesolimbic regions involved in emotions and addiction. However, the precise circuits and molecular basis underlying anxiety associated with chronic opioid use are poorly understood. Using a mouse model, we demonstrated that anxiety-like behaviors appeared in the first two weeks after morphine withdrawal. Furthermore, the BLA and vHip were activated in mice experiencing anxiety after morphine withdrawal (Mor-A). KORs in the BLA to vHip projections were significantly increased in the Mor-A group. Optogenetic/chemogenetic inhibition of BLA inputs ameliorated anxiety-like behaviors and facilitated conditioned place preference (CPP) extinction in Mor-A mice. Knockdown of the BLA to vHip circuit KOR alleviated the anxiety-like behaviors but did not affect CPP extinction or reinstatement. Furthermore, combined treatment of inhibition of the BLA to vHip circuit and KOR antagonists mitigated anxiety-like behaviors and prevented stress-induced CPP reinstatement after morphine withdrawal. These results revealed a previously unknown circuit associated with the emotional component of opioid withdrawal and indicated that restoration of synaptic deficits with KOR antagonists might be effective in the treatment of anxiety associated with morphine withdrawal.